Development of Valid, Practical, and Potential Web-Based Learning Materials for Higher Education - Agustina, Nora; Sutiono, Edi; Adesti, Anita; Susila, Heni Rita (Teknodika, 2023)
The research intends to develop web-based teaching materials. The teaching materials developed have valid, practical elements and potentially affect student learning outcomes. While the product development model used Rowntree, product evaluation employed Tessmer's formative evaluation. This study on development was conducted at Baturaja University. Walkthroughs, interviews, questionnaires, observations, and tests were used as data collection techniques. The results revealed that the third prototype was a valid and practical design when used in learning, with 80% (17 students) following the learning process very well and 20% (three students) following the learning process well. In light of this, it can be inferred that the researchers’ efforts to develop web-based instructional materials using the PHP MySQL program have the potential to be successful.